Pemerkosaan Keadilan Menurut Kajian Hermeneutik Amos 5:7-13 - Monica G. CH. Pakasi; Art Sam; Aan Aan (Tumou Tou, 2021)
This article was written with the intention of understanding the rape of justice that took place in the nation of Northern Israel and how brave Amos was in opposing it. Amos, who witnessed the injustice that was happening there, dared to oppose it and did not close his eyes when he saw the poor being oppressed and treated unfairly. The researcher uses a qualitative method and reviews Amos 5:7-13 with a hermeneutic study to get the message from the text. So from the results of this hermeneutic work, the researcher found that Amos was very brave in opposing injustice even though he was not a professional prophet. He used very strong words in condemning the unjust behavior of the rich, the elders, and the judges. They are supposed to uphold justice, but instead do injustice because they accept bribes from the rich. therefore the poor no longer get protection from those who should protect them from injustice. So, it can be concluded that Amos 5:7-13 wants to criticize the behavior of humans who do injustice to the weak and to those who are seeing injustice happening, but do not dare to oppose it.